Corporate governance in Peru: contribution to refocus the concept - Martínez Ortiz, Juan José (2005)
This paper studies the interactions between majority and minority shareholders and the managers and administrators of Peruvian firms. lt focuses on these interactions by means of the principal-agent problem within a corporate governance scenario employing two dimensions: vertical and horizontal. lt also illustrates the types of costs incurred by the principal in minimizing the agent's extra profit. lt emphasizes the weakness of the legal system in protecting private investors and shareholders.